PEMBUATAN MINYAK KELAPA MURNI (VIRGIN COCONUT OIL/VCO) DENGAN MENGGUNAKAN METODE PEMANASAN - Rachmawati, Nurul Putri; Sari, Myra Wardati (Jurnal TEDC; Vol 17 No 3 (2023): JURNAL TEDCDO - 10.70428/tedc.v17i3.731, 2023)
Virgin Coconut Oil (VCO) is a derivative product of coconut oil which has clear colour, has a low water content and free fatty acid content. The use of VCO has been widely used among the public, either for consumption or internal and external treatment. This study aims to determine the effect of variations in processing (with precipitation and without precipitation) as well as variations in heating temperature (70℃, 80℃ and 90℃) on the quality of VCO (moisture content, peroxide value, acid number and specific gravity). This research was conducted using the heating method and varied the heating temperature, besides that this research also varied the method of precipitation and without precipitation during the process of making VCO. The results of calculations and tests in this study showed that all samples were in accordance with SNI 7381: 2008, the best results in the analysis of water content, namely sample A3 with a value of 0.011%, in the analysis of peroxide number, namely sample B1 with a value of 0.62 meq/Kg, while the analysis free fatty acid content (%FFA) the best results were obtained by sample B1 with %FFA 0.011% and the results of the specific gravity analysis determined the best sample closest to the specific gravity value of market coconut oil, namely sample B2 915.5 Kg/M3. The results obtained from this research are expected to give alternatives variations process for VCO production which are easier and can be carried out by all people.